Current era outcomes of pulmonary atresia with ventricular septal defect: A single center cohort in Thailand - Kanthalas Lertsakulpiriya (2020)
© 2020, The Author(s). Pulmonary atresia with ventricular septal defect (PA/VSD) is a complex cyanotic congenital heart disease with a wide-range of presentations and treatment strategies, depending on the source of pulmonary circulation, anatomy of pulmonary arteries (PAs), and major aortopulmonary collateral arteries (MAPCAs). Data about the outcomes in developing countries is scarce. We therefore conducted a retrospective study to assess survival rates and mortality risks of 90 children with PA/VSD at Siriraj Hospital, Thailand during 2005–2016. Patients with single ventricle were excluded. Survival and mortality risks were analyzed at the end of 2018. The median age of diagnosis was 0.5 (0–13.8) years. The patients’ PAs were categorized into four groups: 1) PA/VSD with confluent PAs (n = 40), 2) PA/VSD with confluent PAs and MAPCAs (n = 21), 3) PA/VSD with non-confluent PAs and MAPCAs (n = 12), and 4) PA/VSD with small native PAs and MAPCAs (n = 17). Of the 88 patients who underwent operations, 32 patients had complete repair at 8.4 ± 4.6 years old. During the follow-up [median time of 5.7 years (7 days-13.6 years)], 17 patients (18.9%) died. The survival rates at 1, 5, and 10 years of age were 95%, 83.7%, and 79.6%, respectively. Significant mortality risks were the presence of associated anomalies and non-confluent PAs.